Global burden of cardiovascular diseases attributable to diet low in vegetables from 1990 to 2021 and forecasting the future trends: a population-based study - Mao, Qingsong; Kong, Yuzhe (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis investigation examines the worldwide impact of cardiovascular diseases (CVD) resulting from inadequate vegetable consumption, based on the 2021 Global Burden of Disease Study data.MethodThe study assessed the global, regional, and national repercussions of low vegetable intake on CVD, with a focus on variations among different age and gender demographics. It further analyzed the correlation between disease burden and the Socio-Demographic Index (SDI), and employed an ARIMA model to predict future trends in CVD associated with insufficient vegetable consumption up to 2050.ResultIn 2021, a diet lacking in vegetables was responsible for roughly 682,400 deaths and 16 million disability-adjusted life years (DALYs) attributed to CVD, indicating a declining pattern over recent year. Individuals aged 75 and older were predominantly affected. Future projections indicate an expected rise in CVD incidence in lower-middle SDI regions, with African nations potentially experiencing increased challenges related to low vegetable consumption by 2030 and 2050.ConclusionThe findings underscore the critical necessity for preventive measures against CVD and emphasize the significance of improving dietary habits, particularly vegetable intake.